An Overview on the Structural Monitoring, Assessment and Retrofitting of Historical Structures with a Focus on 13th Century Monuments - Ilki, Alper; KOÇAK, PINAR İNCİ; Halici, Omer F.; Demir, Cem; CÖMERT, MUSTAFA; Kuran, Fikret (Springer Science and Business Media B.V., 2024)
Monumental historical structures affirm natural and cultural identity and hence they should be transmitted to future generations. The protection and preservation of these structures against aging and natural hazards, particularly seismic actions, requires a comprehensive approach including diagnosis of the present condition of the structure and enhancement of structural capacity for disaster mitigation, if necessary. It is obvious that due to their historical values, any attempt towards the preservation of the monumental historical structures must be carried out with respect to the principles of integrity and authenticity. In this study, the structural performance assessment procedures, implementation of structural health monitoring systems and seismic strengthening strategies are discussed and described with reference to 13th-century monumental historical structures in Turkiye. The structural engineering aspects of recent activities for the restoration and preservation of the Great Mosque and Hospital of Divrigi (a world heritage listed structure) and Sivas Ulu Cami (Mosque) Minaret are briefly presented. In light of the structural analysis and monitoring results, recommendations for interventions to these monumental structures are outlined. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2024.
▪️ Part of the book series: Geotechnical, Geological and Earthquake Engineering ((GGEE,volume 54)).
Keywords: Assessment; Historical structures; Monitoring; Retrofitting; Seismic